Stewardship Theory dalam Tata Kelola Berkelanjutan: Studi Literatur - Ersa Lestari; Maryana Enzelika; Zul Azmi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Sustainability has become a central issue in modern corporate governance. Traditional governance approaches grounded in Agency Theory are considered insufficient to fully explain sustainability practices driven by managerial commitment and internal values. This article aims to examine the role of Stewardship Theory as a conceptual foundation for sustainable governance. This study employs a qualitative approach using a descriptive-analytical literature review of ten national and international scholarly articles sourced from Google Scholar, Scopus, and SINTA. The findings indicate that Stewardship Theory emphasizes intrinsic motivation, long-term orientation, and managers’ moral responsibility, which align with the economic, social, and environmental dimensions of sustainability. Furthermore, organizational and cultural contexts, particularly in Indonesian family firms, strengthen the application of stewardship values in sustainable governance practices. This study concludes that Stewardship Theory serves as a relevant complementary approach to enrich both the theoretical and practical understanding of sustainable corporate governance.